Responses of coastal fishery resources to rapid environmental changes - Heikki Peltonen; Benjamin Weigel (Journal of Fish Biology, 2022)
Coastal systems experience strong impacts of ongoing environmental change, affecting fish communities and subsequently fishery yields. In the Baltic Sea, the combined effects of climate‐induced changes and eutrophication‐related pressures constitute major threats to its living resources. Although much work has been devoted to uncovering environmental impacts on the commercially most valuable fish stocks, only little is known about community‐wide responses of fished species and how environmental change may affect their yield. In this study, the authors use a joint species distribution modelling framework to disentangle environmental impacts on species‐specific fishery yields of 16 fished species along the coast of Finland over four decades. The authors show that environmental covariates substantially contributed to variations in fishery yields and are likely to have strong impacts on fished resources also in the future. Salinity and near‐bottom oxygen concentration emerged as the strongest environmental drivers of yields at the community level, whereas temperature was particularly important for cod ( Gadus morhua ) and sprat ( Sprattus sprattus ) yields. The authors found shore density to be an important predictor for fisheries resources especially for freshwater fish. The results of this study suggest that the changes in environmental conditions during the past four decades had a positive effect on the yields of freshwater and warm‐affinity species, whereas yields of marine cold‐affinity species have been mainly negatively affected by contracting favourable habitats, becoming warmer and less saline.